2022
DOI: 10.33448/rsd-v11i10.32591
|View full text |Cite
|
Sign up to set email alerts
|

Infecções hospitalares em Unidade de Terapia Intensiva: Uma revisão integrativa

Abstract: Descrever os microrganismos mais prevalentes em Unidade de Terapia Intensiva e os principais fatores de riscos dos pacientes que necessitam desse tipo de suporte. Trata-se de uma revisão integrativa da literatura, utilizando as bases de dados Pubmed, Scielo e Biblioteca Virtual em Saúde (BVS). Foram utilizados os descritores controlados “infecção hospitalar”, “UTI” e “cuidado crítico”. Utilizando o operador booleano “AND”. No período de 2017 a 2021. Como critérios de inclusão: estudos primários e artigo comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
1
0
3
Order By: Relevance
“…In addition, this agent has a remarkable ability to form biofilm on medical device surfaces, including metals, plastics, and biotic surfaces. This ability is closely linked to the development of tissue necrosis and the occurrence of ventilatorassociated pneumonia (VAP) [11,10]. A study by Santo et al [12] evaluated the profile of microorganisms isolated from patients admitted to a hospital in Paraná and identified that Pseudomonas aeruginosa (25.0%) was the most prevalent bacterium in tracheal aspirate isolates among Gram-negative bacteria, which corroborates the results found in this study.…”
Section: Source: Prepared By the Author Based On The Database Of The ...supporting
confidence: 84%
See 1 more Smart Citation
“…In addition, this agent has a remarkable ability to form biofilm on medical device surfaces, including metals, plastics, and biotic surfaces. This ability is closely linked to the development of tissue necrosis and the occurrence of ventilatorassociated pneumonia (VAP) [11,10]. A study by Santo et al [12] evaluated the profile of microorganisms isolated from patients admitted to a hospital in Paraná and identified that Pseudomonas aeruginosa (25.0%) was the most prevalent bacterium in tracheal aspirate isolates among Gram-negative bacteria, which corroborates the results found in this study.…”
Section: Source: Prepared By the Author Based On The Database Of The ...supporting
confidence: 84%
“…In infections related to the respiratory system, it was observed that Pseudomonas aeruginosa was the most frequent species, with 22 positive isolates in tracheal aspirate, in addition to 11 cases in bronchoalveolar lavage. This bacterium is described in the literature as an opportunistic pathogen, as it rarely causes pathology in healthy patients, but represents a great threat to critically ill patients in the hospital environment [10]. In addition, this agent has a remarkable ability to form biofilm on medical device surfaces, including metals, plastics, and biotic surfaces.…”
Section: Source: Prepared By the Author Based On The Database Of The ...mentioning
confidence: 99%
“…Entre esses microrganismos, a Klebsiella pneumoniae, bactéria mais prevalente no estudo, é responsável por cerca de um terço de todas as infecções por bactérias Gram-negativas, como infecções do trato urinário, cistite, pneumonia, infecções de feridas, endocardite e septicemia. Este agente etiológico também é responsável por quadros de pneumonia necrosante, abscessos hepáticos pirogênicos e endoftalmite endógena (Sena et al, 2022). Portanto, medidas devem ser propostas para promover o uso racional de antimicrobianos, uma vez que em países em desenvolvimento poucos mecanismos são aplicados para monitorar ações sobre seu uso racional, havendo a necessidade de implementação de ferramentas para monitorar o consumo desta classe de medicamentos (Axente et al, 2017).…”
Section: Resultsunclassified
“…As infecções hospitalares (IH) são um dos maiores desafios da humanidade quando se trata de prestação de cuidados de saúde e segurança do paciente. A IH tem sido caracterizada como qualquer infecção adquirida após a internação do paciente e que pode se manifestar durante a internação ou pós-alta, quando associada à internação ou procedimentos realizados no hospital (Sena et al, 2022).…”
Section: Introductionunclassified